Current gene panels account for nearly all homologous recombination repair-associated multiple-case breast cancer families - Thibaut S. Matis (Nature Portfolio, 2021)
Abstract It was hypothesized that variants in underexplored homologous recombination repair (HR) genes could explain unsolved multiple-case breast cancer (BC) families. We investigated HR deficiency (HRD)-associated mutational signatures and second hits in tumor DNA from familial BC cases. No candidates genes were associated with HRD in 38 probands previously tested negative with gene panels. We conclude it is unlikely that unknown HRD-associated genes explain a large fraction of unsolved familial BC.